Mitochondrial respiration controls neoangiogenesis during wound healing and tumour growth - L. M. Schiffmann (Nature Portfolio, 2020)
During angiogenesis the vasculature switches from a quiescent to a proliferative state. Here the authors show that mitochondrial respiration in endothelial cells controls angiogenesis during development, tumour growth and tissue repair.